Intergenerational transmission of interethnic union formation patterns in Sweden - Celikaksoy, Aycan (Migration Letters, 2012)
This paper explores intergenerational transmission of interethnic union formation behaviour within families. Using register data from Statistics Sweden I find a strong association in union formation patterns between parents and their offspring. This association holds for all levels of individual and parental education and all regions of origin, except for Americans. When countries of origin are categorized according to cultural distance to the Swedish society, the results indicate that parental intermarriage type is important. Decomposing parental intermarriage into detailed categories and separate estimations for each value system indicate that the mechanisms behind intergenerational transmission of union formation patterns vary by value system of the origin country. For individuals with a background from societies that are culturally similar to the Swedish society, all types of parental intermarriage increase their likelihood of intermarriage. However, for individuals from countries that are relatively more distant culturally to the Swedish society, parental intermarriage within the value system does not play a role in the likelihood of their offspring’s intermarriage.